Comparative study of labetalol and nifedipine in management of non- severe preeclampsia and its fetomaternal outcome - Rose, Delphine T.; P., Jeyarani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In developed countries, 16 percent of maternal deaths were attributed to hypertensive disorders. Of hypertensive disorders, the preeclampsia syndrome, either alone or superimposed on chronic hypertension, is the most dangerous. The incidence of preeclampsia in nulliparous populations ranged from 3 to 10 percent. Methods: The present study was conducted at Government Raja Mirasudhar Hospital, Thanjavur Medical College, Thanjavur, Tamil Nadu, India from October 2017 to October 2018. The study consisted of 100 antenatal women with non-severe preeclampsia. The efficacy of labetalol verses nifedipine in its management was studied along with the fetomaternal outcome. Results: In this study, in the labetalol and in the nifedipine groups adequate control of blood pressure was achieved. However, labetalol was well tolerated by our women without much side effects. Conclusions: The present study indicates both labetalol and nifedipine are equally efficacious in the control of hypertension in non-severe preeclampsia. Pathology of the disease was not altered significantly in both the groups. There was no significant difference in the neonatal outcome between the two groups.